Learning to make a difference: Small-scale women farmers in social learning spaces for climate action - Chanyau, Ludwig (Rhodes University, Faculty of Education, Department of Education)
How do women farmers in Africa learn about climate change? What is quality climate change learning for farmers? How do farmers interface new knowledge with their long-held and trusted traditional knowledge? How do we evaluate learning at farm level and beyond? Using Okoli's theory mining review, I untangled a tripartite knot of social learning literature to find Social Learning Theory (SLT) suitable for a study to explore my practical and scholarly curiosity as reflected in the above questions. Wenger's theory of Social Learning emerged as the most appropriate for my research. The second phase of my study explored the climate change learning and practice terrain for small-scale women farmers, analysing the connection between learning, practice, and the resultant value in two case study areas, municipalities in the Amathole District of the Eastern Cape Province of South Africa. In addition to a paper on SLT mining review that unravels and chooses between the strands of social learning, the two case studies resulted in three articles that responded to the study's objectives and the research questions. The thesis is introduced and synthesised through five 'book-end' chapters, as well as through these four articles. What were my findings? In the first case study, in the drought-stricken Raymond Mhlaba Municipality, I gathered the data through individual semi-structured interviews with farmers, extension officers and representatives of the involved organisations. I also conducted a group interview with farmers and analysed documents to supplement interview data. I analysed the data using concepts of Communities of Practice (CoP) and SLT to map out the learning and practice landscape. I discovered a constellation of CoPs interconnected by the shared drive for adaptive water management. The constellation is made up of tertiary institutions, government departments, non-governmental organisations and farmers of varying experiences and competencies, with women emerging as the more proactive gender, and state-led extension services being willing but overstretched and under-resourced. SLT effectively traced the apparent fragmented learning within and outside the CoPs and the sudden and extensive shifts in the CoP boundaries, especially in the context of COVID-19 pandemic lockdowns and the increased adoption of digital learning platforms. Despite the richness and diversity brought by the emergent new learning networks that involve participants in the province and further afield, the adoption of digital learning platforms worsened the existing generational digital divide among farmers. iii In the second case study, in the water scarce Buffalo City Metropolitan Municipality, I adopted the Value Creation Framework (VCF) to conduct an ethnographic evaluation that used semi-structured interviews, participant observation and document analysis of the learning experiences of women farmers in a social movement on agroecology. I found that the farmer-centred learning approach of the movement has created value for the farmers involved, evidenced by the adoption of agroecology by over 2700 members (including new urban farmers who are occupying open spaces typically used as dumpsites). The learning approach has facilitated expansive learning, enhanced resource mobilisation, new collaborations, partnerships, and seed sharing networks. Additionally, it necessitated context-appropriate and transformative changes to intersectional justice issues associated with historical inequalities in access to land and water and gender discrimination, leading to improved practices, new access to markets and improved quality yields. These are examples of immediate, potential, applied, realised, orienting, enabling and transformative as well as strategic value, as defined by the VCF. In reflecting on how women farmers learn in these social learning spaces I elucidate the learning impact pathways and local contextual influences in shifting CoP boundaries, domains, and practices during the climate crisis as it intersects with other compounding factors. I generated insights that could be useful for stakeholders in the agricultural (extension) sector to build better pathways for emancipatory and empowering expansive social learning in contexts characterised by resource constraints, but also by strong women-led agency. Such learning could make a difference and cushion small-scale farming from collapse especially in times of unprecedented changes. The agroecology movement and associated communities of practice explored in this study create transformative social learning spaces that are able to respond to climate change, and hence a model that state-led extension might want to adopt in other resource-constrained contexts.
Keywords: Social learning -- South Africa -- Amathole District Municipality; Value creation; Environmental education -- South Africa -- Amathole District Municipality; Climatic changes-- Study and teaching -- South Africa -- Amathole District Municipality; Communities of practice; Crops and climate -- South Africa -- Amathole District Municipality; Women farmers -- South Africa -- Amathole District Municipality; Farms, Small -- South Africa; Agricultural ecology -- South Africa